Early Start Denver Model Developing Social Skills for Virtual Autism Children - Mousa imran, Hanan; Ali Sayid, Hasan (Al-Adab Journal, 2020)
The study aimed to build an early intervention program, the Denver model, according to behavioral cognitive methods. And knowing the effect of the program on developing social skills for children with virtual autism. To verify this goal, the researcher put the following hypothesis. There are no statistically significant differences between the mean ranks of the members of the experimental group in the pre- and post-applications on a scale. (CASR2-ST) The current research was limited to children with virtual autism disorder registered at the Al-Noor Institute and Basmat Amal Center in the city of Baghdad (2018-2019) To achieve the aims of the research, the experimental design with the two experimental and control groups with pre- and post-testing was used. The research sample was of 18 children with virtual autism disorder distributed on two groups that were equivalent between them in the age, intelligence, and educational level of the parents, the number of hours of using the electronic screens. The hypothetical autism was measured on a scale (CASR2-ST). To achieve the aim of the research, the researcher prepared an early intervention program, according to the Denver model. The program was corrupted from eight sessions with two sessions per week, the time of each session (60-45) minutes. The research required employing appropriate statistical means. After completing the application of the program, the result of the research resulted in there are statistically significant differences between the average ranks of the experimental and controlling group scores on a scale (CASR2-ST) in the post-test and the researcher concluded that the methods of early intervention have a clear effect in reducing hypothetical autism Among children, and through the results, the researcher reached a set of recommendations and proposals.